PROGRAM KESADARAN MITIGASI BENCANA BANJIR BAGI SISWA SMA NEGERI 5 PAREPARE - Muhammad Ihsan; Jabaluddin Hamud; Yusri Prayitna; Erfin Kurniawan; Risman Firman; Nur Afifah Zhafirah; Hariyati Hariyati; Eksanti Rahmi Ramadhani; Nurma Diyanni Mulya (Universitas Ichsan Sidenreng Rappang, 2026)
Flooding is one of the most frequent hydrometeorological disasters in Indonesia and has substantial impacts on communities, including the education sector. Strengthening disaster literacy among school-aged students is an essential strategy for disaster risk reduction. This community engagement program aimed to improve the knowledge, awareness, and preparedness of students at SMA Negeri 5 Parepare regarding flood disaster mitigation through an educational outreach program. The program employed lectures, interactive discussions, educational videos, and learning evaluations using pre-test and post-test assessments. The activity was conducted on January 21, 2025, involving 35 students. Program effectiveness was evaluated using post-test scores and the normalized gain (N-Gain) index. The results showed that the average post-test score reached 89.06, with the highest score of 100 and the lowest score of 70. The average N-Gain score was 0.75 (75.67%), indicating a high level of learning improvement. Furthermore, 25% of participants achieved high improvement, 72% moderate improvement, and only 3% showed no improvement. These findings demonstrate that the outreach program effectively enhanced students’ understanding of flood causes, impacts, mitigation measures, and disaster preparedness.